Renewable energy : a first course - Ehrlich, Robert, 1938- (Boca, Raton, FL : Taylor & Francis, 2013)
'If you are a student in one of the sciences or engineering who has taken a few introductory courses in physics and calculus, I think you'll like this book. That's because it looks at a variety of technologies in renewable energy, and explains things starting with basic principles. It avoids if at all possible technical jargon, and very mathematically advanced approaches found in many books on the subject. It is also not overly long, unlike many other energy books, and its 14 chapters should easily fit within a standard semester, at least in most schools in the United States'--
Includes bibliographical references and index.
Keywords: Renewable energy sources